Fadiga em pacientes submetidos à cirurgia oncológica: uma coorte prospectiva - Oliveira, Murielly Marques de (2015)
INTRODUCTION. Fatigue in patients undergoing cancer surgery is frequent and brings negative repercussions for the operated individual. There are many knowledge gaps about this multidimensional experience and the factors involved in its occurrence and intensity. OBJECTIVE. Evaluate the fatigue of patients undergoing cancer surgery. METHOD. It is an open prospective cohort, with an initial sample of 117 patients (mean age = 51.2 years; 76.9% female; 65.8% lived with a partner, 58.1% brown skin color; 90.6% non-smoking; 70.9% did not undergo neoadjuvant treatment). They were evaluated between 36 and 02 hours before surgery (baseline - T1), and in two follow-ups: (T2) between 12 and 48 hours after surgery and (T3)10days ± 2 days after surgery. After approval by the ethics committees in research of the study sites and informed consent, patients answered the Piper Fatigue Scale-Revised, Perceived Stress Scale, Adaptive Capacity Index, Hospital Anxiety and Depression Scale, Numerical Pain and Sleep Scales; Karnofsky Performance Scale (KPS). RESULTS. The prevalence of fatigue among patients in the preoperative period of surgical oncology was 25.6% (n = 30). Preoperative fatigue was associated with anxiety, depression, stress, sleep disturbance, pain and worse performance status. Of all the instruments applied, KPS showed better characteristics related to accuracy for assessment of fatigue. The incidence of fatigue in T2 and T3 was 32.3% (n = 32) and 22.7% (n = 17), respectively. The average intensity of fatigue was moderate in all evaluations and the affective dimension had significantly higher scores than the other dimensions. Postoperatively, marital status and adaptive capacity were associated with fatigue in T3. Furthermore, it was observed that the adaptive capacity, sleep disturbance and performance status impacted the development of postoperative fatigue. CONCLUSIONS. This longitudinal study provided new evidence in the knowledge of postoperative fatigue, supporting the planning of more effective actions to prevent and treat fatigue and other symptoms. There was gradual reduction of the occurrence of fatigue after cancer surgery. The affective dimension of fatigue was the dimension with greater intensity. In the preoperative phase, emotional aspects (anxiety, depression and stress), pain, sleep and performance status were associated with fatigue, the latter being more important for accuracy. Postoperatively, those without a partner and worse adaptive capacity should be managed more rigorously since they have more fatigue than the other patients. In addition to these factors, sleep and performance status should be investigated since they impact on the evolution of fatigue.